1996
DOI: 10.1093/brain/119.5.1717
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamotomy in parkinsonian monkeys Behavioural and biochemical analysis

Abstract: Nineteen Macaca fascicularis monkeys were divided into four different groups: Group A (n = 3), control; Group B (n = 3), monkeys treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP); Group C (n = 8), animals treated with MPTP in which the subthalamic nucleus (STN) was unilaterally lesioned by kainic acid injection; in Group D (n = 5), the STN was lesioned prior to MPTP administration. Subthalamotomy resulted in a bilateral improvement of tremor, spontaneous activity, bradykinesia (evaluated by a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 59 publications
7
96
0
3
Order By: Relevance
“…However, the mechanisms underlying the effects of STN-HFS remain unclear Dostrovsky and Lozano, 2002;McIntyre et al, 2004a). Because STN-HFS effects have been shown to be functionally equivalent to those of STN lesions (Bergman et al, 1990;Aziz et al, 1991;Guridi et al, 1996;Alvarez et al, 2005), it has been suggested that STN-HFS silences STN neurons (Benazzouz et al, 1993). However, recent modeling and in vivo studies have shown that additional mechanisms, such as activation of the STN afferent and efferent pathways, may be involved, leading to distant synaptic inhibitory and excitatory effects in BG output nuclei (Windels et al, 2000(Windels et al, , 2005Salin et We investigated the mechanisms involved further by studying STN stimulation in rats in conditions comparable with those used in clinical practice: parameters, monopolar stimulation, and awake animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying the effects of STN-HFS remain unclear Dostrovsky and Lozano, 2002;McIntyre et al, 2004a). Because STN-HFS effects have been shown to be functionally equivalent to those of STN lesions (Bergman et al, 1990;Aziz et al, 1991;Guridi et al, 1996;Alvarez et al, 2005), it has been suggested that STN-HFS silences STN neurons (Benazzouz et al, 1993). However, recent modeling and in vivo studies have shown that additional mechanisms, such as activation of the STN afferent and efferent pathways, may be involved, leading to distant synaptic inhibitory and excitatory effects in BG output nuclei (Windels et al, 2000(Windels et al, , 2005Salin et We investigated the mechanisms involved further by studying STN stimulation in rats in conditions comparable with those used in clinical practice: parameters, monopolar stimulation, and awake animals.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In animal models of Parkinson's disease, neuronal activity is increased in the subthalamic nucleus and pars interna of the globus pallidus, 6 and lesions of these structures result in marked improvement in motor function. [6][7][8] These findings have led to the development of surgical procedures for Parkinson's disease that target the subthalamic nucleus and pars interna of the globus pallidus. 9,10 In patients with Parkinson's disease, the creation of lesions in the pars interna of the globus pallidus (pallidotomy) improves contralateral dyskinesia and provides moderate antiparkinsonian benefits.…”
mentioning
confidence: 99%
“…Lesion of the STN increases striatal glutamate levels in normal rats 83 and decreases 6-hydroxydopamine (6-OHDA)-induced elevation of glutamate. 16,83 Moreover, STN ablation in normal primates decreases pallidal 2-deoxyglucose uptake 43 and expression of the gene for glutamic acid decarboxylase 67; 24 together, these observations indicate decreased cellular activity in STN efferent structures.…”
Section: Discussionmentioning
confidence: 94%